Food Aid for Development: Report on the OECD Development Centre Expert Meeting on Scope and Conditions for Improved Use of Food Aid for Development held in Paris on 30th-31st March 1978 - Schneider, Hartmut; Organisation for Economic Co-operation and Development (Paris: Development Centre of the Organisation for Economic Co-operation and Development, 1978)
Two basic hypotheses were posited for this meeting, namely: (1) that food aid does have a developmental potential beyond what has conventionally been made use of, and (2) that to make use of that potential, the experience with food aid had first to be reviewed critically to show the scope and conditions under which improvements in food aid planning and operations could possibly be achieved.
Contains condensations or extracts from the papers presented at the meeting.
Includes bibliographical references: p. 117-118.
ne 21/05/2018
Loans
Keywords: Food relief